The Coronavirus Disease-19 Infection and the Oral Mucosa - Passarelli, Pier Carmine; Santacroce, Luigi; D’Addona, Antonio; Garcia-Godoy , Franklin (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The current coronavirus disease (COVID-19) pandemics induced a modification of daily life and clinical practice. Health care workers, particularly dentists and dental hygienists, have been obliged to limit their activity and to establish new operative protocols. AIM: We aimed to discuss an easy protocol for the prevention of cross-infections in dental settings. METHODS: We revised literature data about COVID-19 and oral health to establish how to work safely with dental patients. RESULTS AND CONCLUSION: A few papers are currently available about the effective prevention of COVID-19 during dental procedures. Most of the revised articles report a potential strong effectiveness of povidone-iodine and its safety for both patients and dental professionals.